2023
DOI: 10.1021/acs.jafc.3c02616
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungus Reshapes Spikelet Microbiome to Reduce Mycotoxin Produced by Fusarium proliferatum through Altering Rice Metabolites

Abstract: Rice spikelet rot disease (RSRD) caused by Fusarium proliferatum seriously reduces rice yield and produces mycotoxins that threaten human health. The root symbiotic endophytic fungus Phomopsis liquidambaris reduces RSRD incidence and fumonisins accumulation in grain by 21.5 and 9.3%, respectively, while the mechanism of disease resistance remains largely elusive. Here, we found that B3 significantly reduced the abundance of pathogen from 79.91 to 2.84% and considerably enriched resistant microbes Pseudomonas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Therefore, Pseudomonas putida should be primarily used for the construction of subsequent synthetic microbial communities. Studies also have demonstrated the potential of Pseudomonas in regulating plant growth and inhibiting diseases, due to the production of a large amount of antimicrobial secondary metabolites [8].…”
Section: Isolation and Identification Of Strains That Inhibit Fusariu...mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, Pseudomonas putida should be primarily used for the construction of subsequent synthetic microbial communities. Studies also have demonstrated the potential of Pseudomonas in regulating plant growth and inhibiting diseases, due to the production of a large amount of antimicrobial secondary metabolites [8].…”
Section: Isolation and Identification Of Strains That Inhibit Fusariu...mentioning
confidence: 99%
“…Previous studies have shown that large synthetic microbial communities (44 isolates) or small synthetic microbial communities (seven isolates) provide similar disease control [30]. Perhaps because the more microorganisms enriched in plants, the higher the resource cost required to maintain microbial growth and reproduction, and the presence of a large number of strains in the community may increase competition between them [8]. Based on the above results, we will further screen synthetic microbial communities with better inhibitory effects from SynM11, SynM12, SynM13, SynM14, SynM15, SynM16, SynM17, and SynM18.…”
Section: Screening Of Synthetic Microbial Communities With Inhibitory...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, ergosterol, β-sitosterol, 5-pentadecylresorcinol, 5-hydroxymethyl-2-furancarboxylic acid, and succinimide were isolated from Aspergillus niger spore powder. Among them, 5-hydroxymethyl-2-furancarboxylic acid showed the most effective antibacterial activity against Agrobacterium tumefaciens T-37, Erwinia carotovora EC-1, and Ralstonia solanacearum RS-2 [ 72 ].…”
Section: Conservation Strategies For Potato Plants---biocontrolmentioning
confidence: 99%